Mudança da paisagem gerada pela expansão urbana, zona norte da cidade de Boa Vista - RR - Criollo Hidalgo, Shirley Johanna (2017)
The problem of accelerated process of urban expansion in recent decades in the city of Boa Vista-Roraima is a worrying situation in the context of conservation of natural resources and changes of landscapes. The urban dynamics of the city underwent great changes, making previously unoccupied areas occupied in areas unsuitable for housing. By means of Remote sensing techniques to analyze the changing landscape of the north side of Boa Vista, in the period from 1996 to 2016. To fulfill those objectives satellite images Landsat 5 TM sensor were used, CBERS and Landsat 8 CCD sensor 2 sensor OLI, which went through a treatment process and helped supervised classification, using the MAXVER procedure to obtain three thematic maps of land use and occupation of the area and identify the temporal analysis of landscape changes. These results were made with the help of ENVI 4.8 and ArcGis 10 software, in addition to field visits and literature review. For the map of use and occupation of the soil it was defined five classes: arboreal vegetation/forest, savanna, water, urban and exposed soil, the maps were generated identifying the areas mentioned within the three periods (1996, 2005 and 2016), seeking through this space representation to facilitate the analysis of the main lines of urban growth and the removal of riparian vegetation along the Cauamé River. It was noted on the maps of each period the urban class did pressure in relation to other classes (32.76% in 1996, 35.05% in 2005 and 2016 38.99%) and the appearance of exposed soil class also indicates a position of possible urban advance. The results include the urban growth rate in percent, for the years 1996 to 2005 increase of 6.97% and for the period of 2005 to 2016 of 11.28% increase. While the decrease of the riparian forest in the neighborhoods near the Cauamé River, considered one of the most important in the city, results were obtained in 1996 of 2.12 km2, for 2005 of 2.02 km2 and finally for the year 2016 a reduction of 1.80 km2. These geographical techniques allowed to understand that the situation of the city can become serious if not public or environmental agencies not to take the necessary actions in time. The importance of this research is to build updated knowledge and information that can help in the future to improve the environmental and urban planning of the city to allow your natural wealth and preserve have sustainable strategies.